Recurrent dermatofibrosarcoma protuberans: A Case report and literature review - K C, Hari Bahadur; Shrestha, Jayan Man; Lohani, Ishwar (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Dermatofibrosarcoma protuberans is a rare soft tissue tumor which is known for its high recurrence behavior. Adequate excision and regular follow up is the current treatment modality. Case report: 42 years male developed multiple nodular lesions on anterior chest wall for which he underwent surgical therapy for five times, but tumor recurred on every occasion. Wide local excision and split skin grafting was performed with negative margin on histopathology. Conclusion: Dermatofibrosarcoma protuberans has high recurrence rate due to its infiltrative growth pattern. Regular follow up is required after surgery during early post-operative period to detect any recurrences.